Impact Assessment of Energy Transition Policy on Air Quality over a Typical District of the Pearl River Delta Region, China - Weidong Chen; Haixian Li; Yun Zhu; Jicheng Jang; Che-Jen Lin; Pen-Chi Chiang; Shuxiao Wang; Jia Xing; Tingting Fang; Jie Li; Qingshan Yang; Kaiming Zheng (Aerosol and Air Quality Research)
Abstract Energy transition policies have been proposed for the two imperative tasks of carbon dioxide (CO2) emissions peaking and air pollution control in the Pearl River Delta (PRD) region in China. This study assesses the impact of the policies on CO2 emissions mitigation and air quality improvements and provides recommendations for policy implementation. Using Shunde District as a case study, we developed the emission inventories of CO2 and air pollutants, projected the trend of CO2 emissions, and estimated the air quality under three energy transition scenarios using the Long-range Energy Alternatives Planning (LEAP) model and the Weather Research and Forecasting-Community Multiscale Air Quality Modeling (WRF-CMAQ) system. The emission inventory revealed that the power, transportation and industry sources were three key sectors of CO2 and energy-related air pollutant emissions, with a combined contribution of more than 90%. The simulation results of energy transition policy demonstrated that CO2 emissions in Shunde would be unable to peak under the current “business as usual” (BAU) policy, while it could peak at 21.58 million tons (Mt) and 21.18 Mt under the energy transition (ET) and the enhanced energy transition (EET) policies, respectively. The concentrations of all index pollutants could meet the Grade II national standards for air quality in 2025, and the Comprehensive Air Quality Index (CAQI) in 2030 could also significantly decrease by 27.0% relative to the 2019 base year under the most stringent energy transition policies. Our study suggests that the local government should consider taking the power, transportation and industry sources as the priority sectors and implementing a stricter energy transition policy as soon as possible in Shunde District of the PRD region in China.